The Influence of Work Discipline on the Performance of State Civil Apparatus (ASN) at the Secretariat of the DPRD Banten Province - Djaka Adiwinata; Sucihati Sucihati; Irawan Irawan; Yulaikah Yulaikah; Suhroji Adha (International Journal of Education, Information Technology, and Others, 2020)
This study aims to analyze the relationship between work discipline and the performance of the State Civil Apparatus. The method used in this research is a survey method, the form of this research is descriptive quantitative. The sampling method is saturated sample in this research is 98 respondents. The data collection method used a questionnaire and documentation study. The analysis technique uses simple linear regression analysis. The results of this study indicate that work discipline has a positive and significant effect on the performance of the State Civil Service Apparatus.